2003
DOI: 10.1097/01.pep.0000096382.65499.e2
|View full text |Cite
|
Sign up to set email alerts
|

Serial Casting vs Combined Intervention with Botulinum Toxin A and Serial Casting in the Treatment of Spastic Equinus in Children

Abstract: Using serial casting in conjunction with BtA may achieve range of motion goals in less time than serial casting alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…Results showed greater improvement in the ankle joint angle, and greater reduction in spasticity in the injection with casting group, which is consistent with studies conducted earlier 10,15-17…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results showed greater improvement in the ankle joint angle, and greater reduction in spasticity in the injection with casting group, which is consistent with studies conducted earlier 10,15-17…”
Section: Discussionsupporting
confidence: 90%
“…Booth et al10 compared 2 groups: 1) the first group received casting every week, 7-10 days after BTX-A injection, until the ankle dorsiflex angle was 20°, 2) the second group received casting every week until the ankle dorsiflex angle was 20°. Results showed that it took a relatively shorter amount of time for the patients in the first group to have their ankle dorsiflex angle become 20°, and their ankle joint conditions improved faster.…”
Section: Discussionmentioning
confidence: 99%
“…The randomized controlled trials (RCTs) found no significant difference in this outcome between casting and BTX-A, 6,20 between casting plus BTX-A and casting alone, 8,18,20 or between casting plus BTX-A and BTX-A alone. 20,21 Gait parameters Children who received casting showed significantly greater improvements in stride length than children who received no casting.…”
Section: Passive Ankle Dorsiflexionmentioning
confidence: 99%
“…casting versus no treatment, casting versus BTX-A, casting plus BTX-A versus casting-only). All but one of these studies 8 were RCTs, although method of randomization was described and truly random (i.e. Jadad Scale: 1 point 26 ) in only two of these studies.…”
Section: What Is the Strength Of The Evidence?mentioning
confidence: 99%
See 1 more Smart Citation